CONSTRUCTION OF THE FUTURE: THE EXPERIENCE OF PHASED IMPROVEMENT OF ENGINEERING EDUCATION - G. E. VESELOV; N. A. LYZ’; A. E. LYZ’ (Высшее образование в России)
The article analyzes the necessity and possibility of achieving a new quality of engineering training. In the light of the society trends, the article considers the guidelines for improving engineering education. The authors systematize the requirements to the educational process ensuring effective development of students’ professional and universal competencies. One of the hindrances is an inadequate readiness of teachers, employers, students to perform new functions. It is concluded that in the face of the unsolved problems, it is advisable to implement a phased transition to a new engineering education. It is necessary to realize at each stage not only the possible at that moment changes in educational process, but also measures that can help to resolve contradictions and create the prerequisites for a successful transition to the next stage. The article describes the most effective measures of the first stage of improving engineering education: the creation of university education-al standards, the use of project-based learning, the contest of lecturers, the independent assessment of educational outcomes, the interaction with employers, the elaboration of a system of activities with schoolchildren and etc.